Gluten Detection by Real-Time PCR: an Alternative for Tracking Processed Foods - Wemerson de Castro Oliveira; Hans Fröder; Eléia Righi (Brazilian Archives of Biology and Technology)
Abstract This work reports a real-time PCR assay to specifically detect the presence of gluten in complex food matrices and to carry out an in-silico prospection of primers used in scientific research. The primers used were “tritprglut” and “Planta 18S” (reference gene), which had mean quantification cycle values (Cq) of 34.30 and 16.98, respectively. The real-time PCR protocol was validated in different meats (beef, chicken, pork, horse and lamb) with an average Cq of 25.69. Tests to verify fraud in industrialized foods were carried out with the following products: cereal bars, chocolate, crackers and two types of snacks. All foods complied with the information contained on the label, except for the cereal bar that was identified as “may contain gluten” and had a “high content” concentration (1,925 mg/kg). The LD value was 36 cycles and the LQ was 60 mg/kg, being within the “low content” classification range. The in-silico tests were performed using two software, MFE and NETprimer, and the content parameters GC, Tm (°C), ∆G (kcal/mol), dimer formation and hairpins. The “Wheat-w-Gliadin” primer showed the best average parameters: size= 24 bp; GC= 44%; Tm = 62.5 °C; ∆G= -32.25 kcal/mol; no dimer or hairpin formation; and a maximum primer rating (100). There were differences in results between the software used. The results highlight the potential of the real-time PCR technique in detecting gluten and/or allergens in foods with a complex matrix, such as chocolate and cereal bars tested in this study, proving to be sensitive and robust to detect the presence of potentially high gluten concentrations. harmful for celiac consumers.